PERMINTAAN TERIGU DI INDONESIA - Bambang Djanuwardi; Ahmad Sutarmadi; Gunawan Sumodiningrat (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1990)
This study on wheat demand in Indonesia attempto know the factors influencing the wheat demand and to what extent it is influenced.The data used in this study is a time series of 1967 to 1986, and regression analysis was employed with static double log model.The result indicates that the price elasticity of demand for wheat is not elastic, while the income elasticity of demand is elastic. The cross price elasticity of demand of rice is not elastic.Variables that consistently influence demand of wheat are, wheat price, rice price, and income. While for sugar, egg, milk, there is no strong eyidencce indicating that they are the wheat complements. It can not be concluded either that corn is the substitut of wheat